2020
DOI: 10.1007/s11156-020-00874-0
|View full text |Cite
|
Sign up to set email alerts
|

Volatility and asymmetric dependence in Central and East European stock markets

Abstract: We study the effects of contagion around the global financial crisis (GFC) and the Eurozone crisis periods using German and UK returns, each paired with returns from Central and East European (CEE) stock markets that recently joined the European Union (EU). Using bivariate vector error-correction models (VECMs) estimated in GARCH(1,1), we find strong support for long-run equilibrium conditions. This finding suggests that tests of tail dependence using differenced VARs may be mis-specified when long-run equilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…The Hansen J-statistic of the over-identifying restrictions showed that the null hypothesis that the instrument's correlations do not affect the error terms cannot be rejected. The results also showed that the model has good instruments by way of revealing the First stage F-statistic (p-value ≤0.01; Joseph et al, 2020). The lagged dependent variable enter the regression was significantly positive, this effectively assumes a system-GMM type model lends empirical support to the hypothesis that, indeed the impact of financial development on international trade deregulation cannot be estimated.…”
Section: System-gmm Regression Estimatesmentioning
confidence: 60%
See 1 more Smart Citation
“…The Hansen J-statistic of the over-identifying restrictions showed that the null hypothesis that the instrument's correlations do not affect the error terms cannot be rejected. The results also showed that the model has good instruments by way of revealing the First stage F-statistic (p-value ≤0.01; Joseph et al, 2020). The lagged dependent variable enter the regression was significantly positive, this effectively assumes a system-GMM type model lends empirical support to the hypothesis that, indeed the impact of financial development on international trade deregulation cannot be estimated.…”
Section: System-gmm Regression Estimatesmentioning
confidence: 60%
“…Kurtosis is always positive and statistically significant at 1% levels across variables. Generally, the existence of kurtosis stipulates evidence for volatility clustering and fattailed (Joseph et al, 2020). The jarque-bera statistics rejected the normality test at the 1% level of Journal of Applied Business and Economics Vol.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…In the context of popularizing IFRS, as well as learning about the mechanisms occurring in the 'relational investor' markets, especially emerging markets, the results showing low market information efficiency after an IPO are important. The more so that, as indicated by Joseph et al (2020), despite the coordinated economic and financial policies of EU members, the markets of Eastern Europe do not show the desired level of market integration. The article has shown that information efficiency is noticeable during IPOs because of the great interest of investors in new companies, but it disappears after the IPO.…”
Section: Discussionmentioning
confidence: 99%
“…Empirically, there is a broad acknowledgment that stock markets can be volatile in developed and developing economies, but studies seem to differ on the level of volatility and persistence. Joseph, Vo, Mobarek, and Mollah (2020) suggest that volatility persists in developed economies than in less developed countries in central and eastern European markets. A similar outlook is expressed in Mallikarjuna and Rao (2019), which hints that stock markets in developed countries are more sensitive to information than their counterparts in developing countries.…”
Section: Introductionmentioning
confidence: 99%